Skills in Family Support: Content Analysis of International Organizations’ Websites - Buciuceanu-Vrabie, Mariana; Mešl, Nina; Zegarac, Nevenka; Kodele, Tadeja (Calitatea Vieții, 2023)
The study is part of a comprehensive research project launched within the framework of COST Action “The pan-European Family Support Network: A bottom-up, evidence-based and multidisciplinary approach” (EurofamNet, code CA18123). In this project, an exercise of mapping international organizations on skills qualification in family support has been developed. The aim of this study was to examine the profile of organizations and analyze their web-provided content to identify, describe and catalogue available data on basic professional skills, promoted, developed, and applied in family support work. The final sample includes 88 international and European organizations working with families with children and youth in various fields (psychology, social work, health, law, etc.) identified by the snowball technique. Using the method of web-content analysis three interconnected maps of bodies in the field were developed, highlighting a general profile of the organizations, and a wide range of important professional skills of family support workforce were specified and ranked. Frequency analyses and contingency tables were carried out. The results show that most of the organizations in the field do not present a plain definition of skills framework listed generally or in a separate document; multidisciplinary approaches to family support skills are not yet common practice; and evaluations of skills or references to a standard framework are limited.